Ethical orientation and choice context of mayoral candidates accused of corruption in Brazil: randomized experiment based on vignettes - Silva, Jorge Otavio de Souza; Rossoni, Luciano; Gonçalves, Clayton Pereira (Frontiers in Political Science, 2025)
Why do voters vote for candidates known for corruption allegations? We herein suggest two possible explanations for it. First, the choice context affects voters’ risk assessment, since voting for a candidate considers other candidates because aversion to extreme alternatives can change their preferences. Second, the judgment, according to which, candidates’ features are relevant, is not impartial because previously defined preferences set the relevant ones. We also seek to assess such judgments from a moral perspective supported by the understanding that individuals presenting utilitarian ethical orientation substantiate their choices of candidates who deliver results for voters. In contrast, individuals accounting for a deontological orientation focus on means and principles. We designed a vignette experiment with 223 respondents who were randomly exposed to two different scenarios in order to assess such elements empirically: two candidates, one newcomer and one experienced candidate whose accounts were disapproved by the court of auditors; three candidates, the two previous candidates and one experienced candidate who was convicted of corruption. Based on the results, the presence of the most corrupt candidate significantly increased the probability of voters voting for the newcomer; thus, the stronger the utilitarian orientation, the greater the likelihood of voters voting for the experienced candidate, mainly when there is a more corrupt candidate in the race.